Twelve Million Smokers Look Online for Smoking Cessation Help Annually: Health Information National Trends Survey Data, 2005–2017. Issue 2 (11th April 2018) - Graham, Amanda L; Amato, Michael S
Abstract: Background: This study quantified the potential reach of Internet smoking cessation interventions to support calculations of potential population impact (reach × effectiveness). Using a nationally representative survey, we calculated the number and proportion of adult smokers that look for cessation assistance online each year. Methods: Five waves (2005, 2011, 2013, 2015, 2017) of the National Cancer Institute's Health Information National Trends Survey were examined. The survey asked US adults whether they ever go online to use the Internet, World Wide Web, or email and had used the Internet to look for information about quitting smoking within the past 12 months. We estimated the proportion and number of (1) all US adult smokers, and (2) online US adult smokers that searched for cessation information online. Cross-year comparisons were assessed with logistic regression. Results: The proportion of all smokers who searched online for cessation information increased over the past decade ( p < .001): 16.5% in 2005 (95% CI = 13.2% to 20.4%), 20.9% in 2011 (95% CI = 15.55% to 28.0%), 25.6% in 2013 (95% CI = 19.7% to 33.0%), 23.4% in 2015 (95% CI = 16.9% to 31.0%), and 35.9% in 2017 (95% CI = 24.8% to 48.9%). Among online smokers only, approximately one third searched online for cessation information each year from 2005 through 2015. In 2017, that proportion increased to 43.7% (95% CI = 29.7% to 58.7%), when an estimated 12.4 million online smokers searched for cessation help. Conclusions: More than one third of all smokers turn to the Internet for help quitting each year, representing more than 12 million US adults. Implications: This research provides contemporary estimates for the reach of Internet interventions for smoking cessation. Such estimates are necessary to estimate the population impact of Internet interventions on quit rates. The research finds more than 12 million US smokers searched online for cessation information in 2017.